PENGEMBANGAN METODE DIORAMA KISAH BERBANTUAN DIMENSI ATRIBUT DENGAN PENDEKATAN EBP (EXPLORATION, BRAINSTORMING, PERFORMANCE) DALAM PEMBELAJARAN PKN - Septiana Agustin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
The Story Diorama is one of lesson method. It consist of many stories or events that memorized by students. Attribute Dimension is a set of equipment used by students in practicing lessons using the Story Diorama method. This study aims to measure the effectiveness of the diorama method with the help of attribute dimensions developed using the EBP (Exploration, Brainstorming, Performance) approach. The research method used in this study is qualitative descriptive. Data collected from observations, pre-tests, and post-tests. The results is the form of a Story Diorama method assisted by Attribute Dimensions developed with the EBP approach. The EBP approach syntax based on the results of the Scientific Approach analysis in 2013 Curriculum and 21st Century Learning Skills. The application of learning using the Diorama of Story method assisted by Attribute Dimensions proved effective and useful for students' knowledge and experience. Because, the essence of effective learning for students is to experience it for real.